Understanding how young children learn : bringing the science of child development to the classroom - Ostroff, Wendy L. (ASCD, 2012)
Human beings are born to learn. During the last few decades, developmental science has exploded with discoveries of how, specifically, learning happens. This provides us with an unprecedented window into children's minds: how and when they begin to think, perceive, understand, and apply knowledge. Wendy Ostroff builds on this research and shows you how to harness the power of the brain, the most powerful learning machine in the universe. She highlights the processes that inspire or propel learning-play, confidence, self-regulation, movement, mnemonic strategies, metacognition, articulation, and collaboration-and distills the research into a synthesis of the most important takeaway ideas that teachers will need as they design their curriculum and pedagogy. Each chapter has suggested activities for exactly how teachers can put theory into practice in the classroom. When you understand how your students learn, you will know how to teach them in ways that harness the brain's natural learning systems. Dr. Wendy L. Ostroff is Associate Professor in the Program for the Advancement of Learning at Curry College.